Sustainable Workshop untuk Meningkatkan Teachers’ Performance dalam Penyusunan Perangkat Pembelajaran - Muhsin, H (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2021)
This study aims to describe the impact of implementing the Sustainable Workshop on increasing teachers' performance in developing learning tools. This study used a supervision-based action research (SbAR) consisting of three cycles to facilitate the implementation of a Sustainable Workshop. The workshop program was attended by 36 teachers from 10 elementary schools in the Central Lombok District Education Office. The data was collected using performance assessment and analyzed based on the percentage scores of teacher's performance in developing learning tools. The results showed that the percentage of completeness in each cycle was obtained 30, 56% in cycle I, 83, 33% for cycle II, and 100% in cycle III. This research concludes that a sustainable workshop has a positive impact in strengthening teachers' understanding in developing learning tools.